LITERASI ARTIFICIAL INTELLIGENCE UNTUK GURU MADRASAH ALIYAH KUN SHOLIHAN - Rudy Cahyadi; Budi Suyanto; Andi Nurkholis; Andrey Ferriyan (Jurnal Padamu Negeri, 2025)
The development of artificial intelligence (AI) technology has brought about significant changes in various aspects of life, including education. AI is now used not only in industry and business but has also penetrated classrooms as a learning aid, personalized material, and even as a learning evaluation system. However, the use of this technology is not yet fully understood and optimally implemented by educators, especially in madrasah environments. Therefore, an AI literacy training program specifically designed for teachers at Madrasah Aliyah Kun Sholihan is needed. This training is expected to improve teachers' understanding of the basic concepts of AI, its application in learning contexts, and practical skills in using various AI-based platforms or applications to support more interactive, effective, and adaptive teaching and learning activities.